Liquid organomineral fertilizer containing humic substances on soybean grown under water stress - Marcelo R. V. Prado; Oscarlina L. dos S. Weber; Milton F. Moraes; Carlos L. R. dos Santos; Morgana S. Tunes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study evaluated the effect of an organomineral fertilizer enriched with humic substances on soybean grown under water stress. The experiment was performed in a greenhouse using a Red Latosol (Oxisol) with adequate fertility as substrate, in which soybean plants were cultivated with and without water stress. The experimental design was randomized blocks, in a 2 x 5 factorial scheme (two moisture levels and five fertilizer doses: 0, 1, 2, 4 and 8 mL dm-3), totaling 10 treatments, with four replicates. The organomineral fertilizer was applied in the soil 21 days after plant emergence and the water regimes were established one week thereafter. The fertilizer was not able to attenuate the effects of water stress, reducing soybean grain yield by more than 50% compared with plants cultivated under no stress. Fertilizer doses caused positive response on soybean nutrition and grain yield and, under water stress condition, the most efficient dose was 5.4 mL dm-3. There were lower leaf concentrations of nitrogen, phosphorus and potassium and higher concentrations of sulfur in plants under stress. Humic substances favor the absorption of micronutrients.